Choke points: logistics workers disrupting the global supply chain (London, 2018)
"Global capitalism is a precarious system. Relying on the steady flow of goods across the world, trans-national companies such as Wal-Mart and Amazon depend on the work of millions in docks, warehouses and logistics centres to keep their goods moving. This is the global supply chain, and, if the chain is broken, capitalism grinds to a halt. This book looks at case studies across the world to uncover a network of resistance by these workers who, despite their importance, often face vast exploitation and economic violence. Experiencing first hand wildcat strikes, organised blockades and boycotts, the authors explore a diverse range of case studies, from South China dockworkers to the transformation of the port of Piraeus in Greece, and from the Southern California logistics sector, to dock and logistical workers in Chile and unions in Turkey."